Identification And Structural Elucidation Of 3-Bromo-10-Camphor Sulphonic Acid In Cucumis Trigonus Roxb - A.BALAKRISHNAN,; R.KOKILAVANI, (International Journal of Pharma and Bio Sciences, 2012)
The fruit extract of Cucumis trigonus Roxb of family Curcurbitaceae was subjected to isolation and identification of chemical constituents. The extract was purified and isolated by column chromatography and thin layer chromatography (TLC). The isolated compound was then subjected to Infra red spectroscopy (IR) for identification of functional groups, 1H NMR and 13C NMR for identification of protons and carbon atoms. LCMS and elemental analysis were done to identify the molecular weight and elemental composition of the isolated compound. From the spectra obtained from IR, 1H NMR and 13C NMR, LCMS and elemental analysis, the isolated compound was found to be 3-Bromo -10- camphor sulphonic acid (C10H17BrO5S) with a molecular weight of 329.